Hospital admissions among immigrants from low-income and foreign citizens from high-income countries in Spain in 2000-2012 - José M. Ramos; Héctor Pinargote; Eva M. Navarrete-Muñoz; Alejando Salinas; Jaume Sastre (Springer, 2019)
Over the last decade, the number of foreign nationals in Spain has increased. Our aim was to report the trends in hospital admissions, differentiating between foreign nationals from high-income countries (HICs) and from low- and middle-income countries (LMICs) in a public hospital. A retrospective analysis of hospital admissions in patients aged ⩾15 years between 2000 and 2012 was performed by means of hospital information systems at a public hospital in the city of Alicante, Spain. During the period of the study, 387,862 patients were admitted: 32,020 (8.3%) were foreign, 22,446 (5.8%) were from LMICs, and 9574 (2.5%) were from HICs. The number of foreign nationals, foreign nationals from LMICs, and foreign nationals from HICs admitted increased from 1019, 530, and 489 in 2000 to 2925, 2097, and 828, respectively in 2012. A total of 27.5% of patients were admitted for pregnancy, childbirth, and puerperium, especially foreign nationals from LMICs (34.3%), and 14.1% of foreign nationals were admitted for cardiovascular diseases (14.1%), which were more common in those from HICs (26.3%). The number of admissions among foreign nationals from LMICs increased significantly in all the diagnoses, but in pregnancy, childbirth, and puerperium, the increase was higher. In conclusion, nearly one out of 10 adult patients admitted to our hospital was foreign, mainly from LMICs, and the main reason for admission was diagnoses related to pregnancy, childbirth, and puerperium.